WILAYAH INTI DAN WILAYAH EKONOMI NEGARA INDONESIA - Natalia, Jupita; KUSTIAWAN; JUPITA NATALIA; AULIA AGUSTIN; WIKY DWIPA ABIAL (Paradigma Mandiri : Jurnal Pengabdian Kepada Masyarakat, 2024)
Core regions and economic regions are two important geographic concepts in the context of regional development and economic growth of a country. In Indonesia, these two concepts have significant relevance in determining sustainable and equitable regional development policies throughout the archipelago. The core area usually refers to the area or area that is the center of government, economy and culture of the country. In Indonesia, Jakarta is often considered a core region, with a large concentration of infrastructure, economic activity, and a high population. On the other hand, economic regions include areas that have high economic growth potential and significant contributions to national production. In Indonesia, important economic regions include West Java, Central Java, East Java, as well as other areas that have rapidly developing industry, such as North Sumatra and East Kalimantan. The difference between core regions and economic regions highlights the complexity of Indonesia's regional structure which consists of various levels of economic development, infrastructure access, and development inequality. The importance of a deep understanding of these differences is to design effective and sustainable development policies that can encourage inclusive economic growth throughout Indonesia. This includes investment in basic infrastructure such as transport and communications, development of local industry, and empowerment of local communities. With a comprehensive approach to core areas and economic areas, Indonesia can achieve sustainable economic growth that benefits all levels of society and brings prosperity to the entire country.